2004
DOI: 10.1023/b:card.0000041245.61136.56
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR/p70S6KSignal Transduction Pathway Plays a Role in Cardiac Hypertrophy and Influences Expression of Myosin Heavy Chain Genes in vivo

Abstract: The data suggest that an intact mTOR signaling pathway is required for rapid hypertrophic growth of the heart in vivo. Moreover, the data suggest a novel link between the mTOR/p70(S6K) signal transduction pathway and pretranslational control of myosin gene expression in the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…However, PA can also activate mTORC1, leading to the downstream activation of p70S6 kinase ( 58,59 ), which phosphorylates and activates S6 ribosomal protein to promote cell growth ( 58,59 ). In fact, activation of mTORC1-p70S6 kinase leads to cardiac hypertrophy ( 79 ). We now show that there is an increase in signaling downstream of mTOR, i.e., increased p70S6 kinase phosphorylation in combination with a 14-fold increase in S6 ribosomal protein activation.…”
Section: Examination Of the Downstream Signaling Effects Of Aberrant mentioning
confidence: 67%
“…However, PA can also activate mTORC1, leading to the downstream activation of p70S6 kinase ( 58,59 ), which phosphorylates and activates S6 ribosomal protein to promote cell growth ( 58,59 ). In fact, activation of mTORC1-p70S6 kinase leads to cardiac hypertrophy ( 79 ). We now show that there is an increase in signaling downstream of mTOR, i.e., increased p70S6 kinase phosphorylation in combination with a 14-fold increase in S6 ribosomal protein activation.…”
Section: Examination Of the Downstream Signaling Effects Of Aberrant mentioning
confidence: 67%
“…11,12,14 As in our study, ␤-MHC was reported to be increased after rapamycin, suggesting a stress response of the cardiomyocytes. 12,15 In contrast, studies with rapamycin reported either preserved function or protection from overload-induced dysfunction. 11,12 This discrepancy might be explained by the dosing and timing of the rapamycin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] However, other studies have challenged the importance of mTOR-mediated protein synthesis and growth. For example, deletion of the ribosomal S6 kinases, direct downstream effectors of mTOR, did not attenuate pathological, physiological, or insulin-like growth factor receptor-induced cardiac hypertrophy.…”
Section: Clinical Perspective On P 1082mentioning
confidence: 99%
“…Role of mTOR inhibition on LVH: Some experimental studies have demonstrated the efficacy of the mTOR inhibitor SRL in the regression of LVH in transverse aortic constriction animal models. 8,12) The rationale of these studies lies in the inhibitory effect of SRL on the mTOR/p70 S6 kinase signal transduction pathway, 9) which plays a central role in cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…6) The mammalian target of rapamycin (mTOR) pathway plays a central role in regulating mRNA translation and cell growth, 7) and an mTOR inhibitor, sirolimus (SRL), has been demonstrated to decrease LV mass (LVM) in experimental animal models. [8][9][10][11][12] Clinical studies also showed that SRL had an advantage in the improvement of LVH compared with conventional calcineurin inhibitors (CNI) when used as an immunosuppressant in heart or kidney transplant recipients. [13][14][15] However, little is known about how the next generation mTOR inhibitor derivative everolimus (EVL) affects LVM.…”
Section: Eft Ventricular Hypertrophy (Lvh) Is Observed In Pa-mentioning
confidence: 99%